THE EFFECT OF ABDOMINAL STRETCHING EXERCISE ON THE INTENSITY OF DYSMENORRHEA - Nurfitri Nurfitri; Andi Rizky Amaliah; Nour Sriyanah (Universitas Islam Negeri Alauddin Makassar, 2021)
Aim: to assess the effect of abdominal stretching exercise on the reduction of intensity of dysmenorrhea in adolescent girl students at the State Senior High School. Method: This study was a quasi-experiment using a pretest-posttest research design with a total of the study samples were 40 respondents by purposive sampling technique. Assessment of the effect of abdominal stretching exercise was carried out before and after 8 abdominal stretching exercise trials. The gathered data were processed and analyzed using the paired samples t-test using IBM SPSS statistical software, version 26. Results of the present study demonstrated a significant effect of abdominal stretching exercise on the reduction of dysmenorrheal intensity (P < 0.05). Discussion The effects of high-intensity exercise on progesterone, prostaglandin metabolites (13,14-dihydro-15-keto-prostaglandin F2 alpha (KDPGF2α), TNF-α, and pain intensity were found to be increased in progesterone and decreased KDPGF2α, TNF-α, and pain intensity after exercise high intensity is relative without exercise. The mechanisms underlying high-intensity exercise-induced analgesia use hormones (progesterone) and cytokine-mediated mechanisms to reduce pain associated with primary dysmenorrhea. Conclusion: abdominal stretching exercise significantly reduced the intensity of primary dysmenorrhea in adolescent girl students. Therefore, abdominal stretching exercise is beneficial to be used as an alternative method in reducing intensity of dysmenorrhea in adolescent girls.